KONJUNGTOR DAN PREPOSISI DALAM RUBRIK â€œTAJUKâ€ SURAT KABAR LAMPOST - Wildasari, Rika; Tarmini, Wini; Fuad, Muhammad (FKIP Universitas Lampung, 2013)
The purpose of this study was to describe conjunction and prepositions within the rubric of